Targeting multidimensional nociceptor-tumor interactions to mitigate immune evasion of cancer - Aojia Jin; Jiaxing Pan; Jingyi Su; Shutong Lin; Xiaohan Shi; Yu Zhang; Jing Feng; Bruno De Geest; Twan Lammers; Tong Ji; Gang Jin; Zhiai Xu; et al. (Science Bulletin, 2026)

Identification of paleo-oceanic core complexes in the Central Asian Orogenic Belt: A case study of the Hongguleleng ophiolite in northern Xinjiang - Zhengyu Yang; Xiaohan Gong; Tianyi Li; Qisong Luo; Riccardo Tribuzio; Huixi Lin; Jifeng Xu (Science China Earth Sciences, 2026)

Morphotectonic characteristics of the Xiongpo anticline in the southwestern Sichuan Basin, China: Implications for active folding mechanisms - Xiaohan Yin; Gang Rao; Lin Gao; Yan Wu; Yaqi Zhong; Pengcheng Tang; Renfu Wang (Geomorphology, 2026)

Effects of partial KCl substitution for NaCl combined with LAB inoculation on the overall quality of Chouguiyu: A study based on safety, bacterial community structure, and flavor characteristics - Xiaohan Jia; Qixuan Pei; Bingrui Guo; Ning Zhao; Ying Yue; Hao Liu; Wei Ji; Shimiao Wang; Xianhao Zhang; Yingxi Chen; Ningbo Qin; Xinping Lin (Food Research International, 2026)

Structural modifications triggered by environmental stress improve bioactivities of exopolysaccharide from endophytic bacterium Methylorubrum sp. Y19 of Taxus cuspidata - Junbo Liang; Xiaohan Zhang; Lin Zhu; Jing Luan; Keyu Sun; Jing Wang; Shuhong Ye (Food Bioscience, 2026)

Maneuver-Aware Residual Multi-Scale LSTM for Short-Term Vessel Trajectory Prediction in Port-Approach Waters - Xinyue Lin; Xiaohan Zhang; Wendong Bao; Yawen Duan; Jiansen Zhao (Journal of Marine Science and Engineering, 2026)
Accurate short-term vessel trajectory prediction is important for traffic monitoring and collision-risk screening in port-approach waters, where vessels frequently turn, accelerate, decelerate, and merge into traffic lanes. This study develops a maneuver-aware residual multi-scale long short-term memory (LSTM) framework for Automatic Identification System (AIS)-based 10–30 min trajectory prediction. The method predicts residual displacement relative to the last observed position, constructs maneuver-aware features from local displacement, course variation, speed variation, turning rate, and acceleration-like terms, and compares fixed and maneuver-guided multi-scale fusion strategies. Experiments are conducted on public AIS data from San Francisco Bay and adjacent approach waters using Maritime Mobile Service Identity (MMSI)-level train/validation/test splits and three random seeds. The largest observed gains come from residual prediction and maneuver-aware features. In the three-seed main evaluation, the fixed multi-scale LSTM (Fixed-MS-LSTM) provides the strongest 10 min accuracy, while the maneuver-guided multi-scale residual LSTM (MGMS-RLSTM) achieves lower average displacement error (ADE) at 20 and 30 min and learns distinct temporal-scale preferences across straight, turning, and speed-changing samples. Encounter-oriented closest point of approach (CPA) and time to closest point of approach (TCPA) evaluation further shows that the residual multi-scale models support more accurate CPA/TCPA-based high-risk screening under the evaluated benchmark. These findings indicate that maneuver-guided fusion can be characterized as a horizon-dependent scale-selection mechanism that complements the fixed multi-scale counterpart.

Development of a scientific version TPS workflow for BNCT dosimetry based on DICOM and Monte Carlo engine - Yinan Zhu; Zuokang Lin; Guanchao Wu; Zhiyuan Lin; Zijian Zhang; Ye Dai; Haiyan Yu; Xiaohan Yu (Physical and Engineering Sciences in Medicine, 2026)

Precise structural characterization and therapeutic potential of a glucomannan polysaccharide from dried rhizome of plant Bletilla striata against ulcerative colitis - Huidan Hou; Lifeng Li; Tahidul Islam; Jingchun Shi; Mengyang Hou; Siliang Jiang; Xiaohan Zhao; Chengyuan Lin; Quanbin Han; Lin Zhu; Zhaoxiang Bian (Carbohydrate Polymers, 2026)

Corrigendum to “Effect of BmPriL on the development of silk glands in silkworm” [J. Insect Physiol. 170 (2026) 104971] - HuaiRong Lin; Nuo Chen; Xiaohan Jiang; Shuxin Qiu; Niewang Ju; Qingyou Xia; Liang Jiang; Huizhen Guo (Journal of Insect Physiology, 2026)

Effect of BmPriL on the development of silk glands in silkworm - HuaiRong Lin; Nuo Chen; Xiaohan Jiang; Shuxin Qiu; Niewang Ju; Qingyou Xia; Liang Jiang; Huizhen Guo (Journal of Insect Physiology, 2026)

Evaluating the role of onboard carbon capture and storage system in remedial unit balancing under the IMO net-zero framework: Insights from GFI and 4E analysis - Yihang Zhou; Shuai Deng; Zhen Tian; Ke Li; Meng Lin; Li Zhao; Chunfeng Li; Xiaohan Zhao; Yijiang Tian; Wenjing Zhang; Min Shi (Journal of Cleaner Production, 2026)

Structural characterization and neuroprotective effect of coix seed polysaccharides - Yini Lin; Xiaohan Ge; Meiru Mao; Jiawen Liu; Zixin Jin; Yi Wang (Food Bioscience, 2026)

HDAC5 mediates the regulation of muscle-derived interleukin 6 on the differentiation of porcine intramuscular pre-adipocytes - Weimin Lin; Hongbing Song; Chongfan Du; Jing Wang; Xiaohan Zhang; Chu Yang; Tianfang Xiao; Ruiyi Lin (Domestic Animal Endocrinology, 2026)

Fixel-based analysis to detect early fiber-specific white matter alterations in sporadic patients with amyotrophic lateral sclerosis - Mingjie Ma; Qingguo Ren; Xiaohan Sun; Pengfei Lin; Wei Li; Yuying Zhao; Xiangshui Meng; Chuanzhu Yan; Shuangwu Liu (Brain Imaging and Behavior, 2026)

Ultra-high SERS-active nanowires-PTFE composite substrate for trace detection of Aflatoxin B1 in aquaculture water - Liu Wang; Jie Han; Liangyan Sun; Jinru Feng; Xiaohan Lin; Daoliang Li; Cong Wang (Journal of Hazardous Materials, 2026)

Near-full-component sewage sludge valorization via integrated alkali-mediated pyrolysis and sub-boiling temperature crystallization of hierarchical carbon-zeolite composites from carbonaceous and inorganic constituents - Zhihang Yuan; Houmin Yin; Jicui Cui; Changfu Yang; Zhou Zhen; Xiaohan Cui; Yumeng Jin; Lifeng Lin; Long Kong; Ruina Zhang; Ruyi Wang; Lei Che; et al. (Water Research, 2026)

Engineering robust yet dissociable phase-separated nanodomains to yield mechanically robust elastomers and elastic fibers for cryogenic applications - Yidi Zhuang; Yuqin Wang; Jing Kang; Lin Ma; Xiaohan Wang (Chemical Engineering Journal, 2026)

PTIP inhibits proliferation, migration, and angiogenesis of retinal microvascular endothelial cells in a high-glucose environment - Jinfeng Zhang; Xiaohan Zhang; Changhua Gao; Cuiting Huang; Xuesong Lin (In Vitro Cellular & Developmental Biology - Animal, 2026)
The abnormal proliferation, migration, and angiogenesis of retinal microvascular endothelial cells (RMECs) are key pathological mechanisms involved in diabetic retinopathy (DR). This study aims to investigate the regulatory role of PAX interacting protein 1 (PTIP) in modulating proliferation, angiogenesis, and inflammatory responses in RMECs under high-glucose conditions. The levels of PTIP, VEGF, MDA, and SOD were measured in RMECs cultured under both normal and high-glucose conditions. A PTIP overexpression vector and a PTIP interference vector were constructed and transfected into RMECs exposed to high glucose. Cell proliferation was assessed using the CCK-8 assay, cell migration capacity was evaluated through wound healing assays, and tube formation ability was analyzed using Matrigel-based assays. Intracellular MDA and SOD levels were determined biochemically, while TNF-α and IL-6 concentrations in the culture supernatants were quantified by ELISA. The expression levels of EGR3, VEGF, MMP3, and MMP9 were detected using Western blotting and immunofluorescence techniques. The results showed that the expressions of PTIP and SOD were down-regulated in RMECs exposed to high glucose, whereas the levels of VEGF and MDA were up-regulated. Overexpression of PTIP in high-glucose-treated RMECs significantly suppressed cell proliferation, tube formation, and migration abilities. Additionally, it markedly reduced the levels of MDA, IL-6, TNF-α, EGR3, VEGF, MMP3, and MMP9 while increasing the level of SOD. Conversely, PTIP knockdown in RMECs under high-glucose conditions elicited opposite effects. Thus, overexpression of PTIP mitigated the impairment of proliferation, migration, and tube formation abilities, as well as reduced the inflammatory response induced by high glucose in RMECs.

Improved Madden–Julian oscillation simulation using the modified moist physical parameterizations for a global climate model - Xiaohan Li; Yanluan Lin; Xiao Zhou; Yiran Peng; Xiaomeng Huang (Climate Dynamics, 2026)

Three-dimensional molecular engineering of fluorene-based self-assembled monolayers for high-performance inverted perovskite solar cells - Fen Xia; Xiaohan Lin; Jing Zhang; Jun Yin; Jing Li; Xijiao Mu; Song Tu; Binghui Wu; Nanfeng Zheng (Chemical Engineering Journal, 2025)

miR-155 aggravates inflammation in MRSA pneumonia by modulating macrophage polarization - Yunfeng Shi; Xiaohan Shi; Yang Yang; Xiaona Lin; Yuhang Pan; Benquan Wu (Molecular Biology Reports, 2025)

Retrieving soil heavy metal concentrations using hyperspectral remote sensing images based on three-band indices at a coal mine in China - Haorui Bai; Bin Guo; Lin Pei; Bo Zhang; Pingping Luo; Tengyue Guo; Min Wu; Xiaohan Ma (Advances in Space Research, 2025)

Multi-scale influence of urban green space vegetation on deposition and diffusion of atmospheric particulate matter: Implications for functional design - Xiaohan LI; Zihan Xi; Lin Zhang; Chuanwen Wang; Danchen Yang; Dongyang Gao; Tian Gao; Ling Qiu (Urban Forestry & Urban Greening, 2025)

Innovative Sargassum fusiforme polysaccharide composites for cryoprotection of large yellow croaker (Larimichthys crocea) fillets during frozen storage - Jiwei Zhu; Yi Guan; Cuirong Luan; Xiaohan Lin; Zhiyu Li; Shuji Liu; Yijing Wu; Jie Yang (Food Chemistry, 2025)

Pectinase from Bacillus velezensis W6: A low pectin-methylesterase activity pectinase for enhancing quality and safety in Orah Mandarin wine and its mechanism for methanol reduction - Yonggang Du; Yuxuanwen Zhao; Xiaohan Wei; Yujiao Zhang; Yiwei Dai; Yingxi Chen; Chaofan Ji; Xinping Lin; Sufang Zhang (Food Bioscience, 2025)

Macrophage-targeted lipid nanoparticles based on Dendron-like lipids deliver mTOR inhibitor to alleviate systemic lupus erythematosus - Keqian Du; Guantao He; Fujian Huang; Xi Zhang; Xiaohan Zhang; Junjin Jie; Chan Huang; Yuqiong Wu; Huiyang Fan; Zhiming Lin; Lin-Ping Wu (Chemical Engineering Journal, 2025)

Efficient carbon/phosphorus recovery from sludge anaerobic fermentation with recyclable MOF-based conductive materials activating sodium persulfate - Long Chen; Jianming Zhu; Ziwei Lin; Xiaohan Zhi; Zimu Qin; Hongtao Zhu (Resources, Conservation and Recycling, 2025)

Seasonal characteristics, source apportionment and ecological risk assessment of priority and emerging contaminants using passive samplers in the coastal water - Zishan Diao; Xianyin Ping; Xue Zhang; Bin Hui; Fanping Zhu; Yiqiao Zhang; Jing Wang; Yinjie Yu; Lin Zhang; Wenjia Hui; Xiaomin Xie; Xiaohan Zhang; et al. (Journal of Hazardous Materials, 2025)

Denitrification dominates nitrate attenuation and nitrous oxide effluxes under water table fluctuations - Lin Zhang; Helin Wang; Xiaohan Liu; Hongbin Zhan; Uwe Schneidewind; Stefan Krause; Menggui Jin; Xing Liang; Yanfeng Liu; Ping Li (Journal of Hazardous Materials, 2025)

Sphagnum cultivation enhances soil carbon stock by alleviating microbial phosphorus limitation - Dan Xue; Huai Chen; Xiaohan Yang; Jennifer Ene Idoko; Lin Wu (Agriculture, Ecosystems & Environment, 2025)

Protease-hydrolysis-driven approach towards the quantification of cellular mRNA after drug treatment in protein nanopores - Ling Zheng; Jizhen Lin; Wenqiang Tian; Ting Weng; Xu Wang; Lan Sun; Chaker Tlili; Xiaohan Chen; Junzhong Lai; Baoquan Zhao; Deqiang Wang (Analytica Chimica Acta, 2025)

Deriving leaf-scale chlorophyll index (CIleaf) from canopy reflectance by correcting for the canopy multiple scattering based on spectral invariant theory - Chenpeng Gu; Jing Li; Qinhuo Liu; Hu Zhang; Alfredo Huete; Hongliang Fang; Liangyun Liu; Faisal Mumtaz; Shangrong Lin; Xiaohan Wang; Yadong Dong; Jing Zhao; et al. (Remote Sensing of Environment, 2025)

Enhanced selective sorption of Cu(II) from washing solution of fly ash using polyethyleneimine-crosslinked chitosan sorbents - Yu Gong; Zitao Lin; Jing Yang; Yongming Ju; Dorota Kołodyńska; Jie Liu; Xiaohan Shan; Yujie Wang; Yong Zhang; Weixin Li (Chemical Engineering Journal, 2025)

Oxygen-vacancy-rich Ni/CeO2: UiO-66-derived high-efficiency catalyst for low-temperature CO2 methanation - Yidan Li; Yahui Yang; Zhenzhen Huang; Huilin Zhou; Riying Zeng; Xiaohan Lin; Xiuling Ma; Lihua Wang; Shengchang Xiang; Zhangjing Zhang (Chemical Engineering Journal, 2025)

Structural and (U-Th)/He thermochronological constraints on the Longmen Shan thrusting-gliding klippes, eastern margin of Tibetan Plateau - Xiaohan Lin; Danping Yan; Liang Qiu; Zhicheng Zhou; Huajie Song; Fei Kong; Chao Du (Science China Earth Sciences, 2025)

Molecular characterization of a novel mycovirus from Curvularia lunata in China - Bin Ke; Xiaohan Mo; Mengting Wu; Lin Wang; Ru Peng; Yuwen Lu; Jiejun Peng; Shaofei Rao; Guanwei Wu; Jianping Chen; Fei Yan; Hongying Zheng (Archives of Virology, 2025)

Historical climate change influenced the phylogeographical patterns of the brown alga Colpomenia sinuosa in the southern China - Xiaohan Song; Jie Zhang; Yuqun Du; Shuang Li; Yiping Shen; Yude Lin; Zimin Hu; Delin Duan (Algae, 2025)
Historical climate changes significantly influenced the phylogeographical patterns of intertidal macroalgae. The brown alga Colpomenia sinuosa was common in warmer waters worldwide, providing an ideal model for genetic diversity and distribution research. C. sinuosa has abundant biomass in the coastal South China Sea, which is a well-known hotspot on marine biodiversity. Here, we analyzed its population structure and demographic history using mitochondrial cox3, atp6, and chloroplast rbcL. We detected a genetic diversity pattern of high haplotype diversity and low nucleotide diversity at the intraspecific level, and our results revealed 2 main clades within C. sinuosa with obvious genetic differentiation among most populations. Furthermore, we detected 5 genetic lineages in concatenated dataset, and the regional isolation was regarded as dominating factor for genetic differentiation. The demographic history suggested that C. sinuosa was first diverged in late Oligocene, then underwent dynamic changes during the Pleistocene. Historical vicariance caused by Pleistocene glaciation events may account for present phylogeographic pattern. Moreover, ocean current and coastal topography of northern South China Sea might participate in shaping present genetic structure. Utilizing C. sinuosa as a model material, we suggested that Dongfang in southwestern Hainan and Sanya in southern Hainan should be regarded as independent management units and give priorities to seaweed resource conservation. In the future, we’ll enlarge our study range and sample collection, and further investigate the genetic distribution pattern of C. sinuosa at larger scale. Our study enriched insights into the historical glacial influences on seaweed phylogeographical patterns, and provided theoretical evidence for seaweed management of southern China.

Effects of plant species on reverse osmosis concentrate treatment in constructed wetlands: Performance, plant growth, and microbial community structure - Jie Wang; Tengfei Hu; Xiaohan Wei; Bin Xu; Xiaoyu Liu; Xiaoliang Zhai; Lin Chen; Wenxian Wang; Wenming Song; Shu Chen; Lihua Cheng; Xiaolin Zhou (Journal of Water Process Engineering, 2025)

High toughness and programmable strength in ion gels via hydrogen bond-induced microphase separation - Qi Wang; Liangke Lin; Tao Zhang; Zhe Wang; Xiaohan Liu; Qi Quan; Guohang Zhang; Yuanjie Zhou; Jiangwei Li; Xiaoyan Zhou; Minzhi Chen (Chemical Engineering Journal, 2025)

Burnt Cervidae bones and sedimentary environments at Luotuodun, Jiangsu Province, China: New insights for Neolithic human behavior - Xiaohan Zhang; Bin Zhou; Jianqiu Huang; Liugen Lin; Michael E. Meadows (Quaternary International, 2024)

A novel spatiotemporal urban land change simulation model: Coupling transformer encoder, convolutional neural network, and cellular automata - Haiyang Li; Zhao Liu; Xiaohan Lin; Mingyang Qin; Sijing Ye; Peichao Gao (Journal of Geographical Sciences, 2024)

Self-circulating pulse alternating ventilation composting technology: Biotic and abiotic effects of mature compost on humification during food waste composting - Lin Zhu; Yiqing Ji; Haining Huang; Liyuan Liu; Xiaohan Wang; Xiangwu Yao; Baolan Hu (Chemical Engineering Journal, 2024)

Di-(2-ethylhexyl) phthalate and its metabolites research trend: a bibliometric analysis - Hyonju Ri; Ying Zhu; Hyonsu Jo; Xiaohan Miao; Unsim Ri; Jianli Yin; Liting Zhou; Lin Ye (Environmental Science and Pollution Research, 2024)

Fungi play a crucial role in sustaining microbial networks and accelerating organic matter mineralization and humification during thermophilic phase of composting - Lin Zhu; Xiaohan Wang; Liyuan Liu; Boyi Le; Chunxu Tan; Chifei Dong; Xiangwu Yao; Baolan Hu (Environmental Research, 2024)

TRIM38 suppresses migration, invasion, metastasis, and proliferation in non-small cell lung cancer (NSCLC) via regulating the AMPK/NF-κB/NLRP3 pathway - Kaihua Zhang; Guihu Lin; Zhenkai Nie; Shan Jin; Xiaohan Bing; Zhantao Li; Mingru Li (Molecular and Cellular Biochemistry, 2024)

Low-intensity alternating ventilation achieves effective humification during food waste composting by enhancing the intensity of microbial interaction and carbon metabolism - Lin Zhu; Chunxu Tan; Xiaohan Wang; Liyuan Liu; Chifei Dong; Zhenyu Qi; Meng Zhang; Baolan Hu (Chemosphere, 2024)

Co-exposure of polystyrene nanoplastics and copper induces development toxicity and intestinal mitochondrial dysfunction in vivo and in vitro - Jinyu Rong; Chenwei Yuan; Xiang Yin; Xiaohan Wu; Fei He; Yixin Wang; Kelvin Sze-Yin Leung; Sijie Lin (Science of The Total Environment, 2024)

Dynamic changes of microbiota and metabolite of traditional Hainan dregs vinegar during fermentation based on metagenomics and metabolomics - Xiaohan Yu; Chunhe Gu; Xiaoxue Guo; Ruijia Guo; Lin Zhu; Xinrong Qiu; Jun Chai; Fei Liu; Zhen Feng (Food Chemistry, 2024)

Studies on regional ozone formation sensitivities and transport with higher spatiotemporal resolutions in a stereoscopic dimension: GEMS and vertical observations - Haochen Peng; Chengzhi Xing; Yikai Li; Chengxin Zhang; Jinan Lin; Jingkai Xue; Xiaohan Wang; Yuhang Song; Xinhan Niu; Cheng Liu (Atmospheric Research, 2024)

Abnormal brain functional network dynamics in amyotrophic lateral sclerosis patients with depression - Sujuan Sun; Yujing Chen; Bing Zhao; Jun Zhu; Tianrui Wen; Bingnan Peng; Qingguo Ren; Xiaohan Sun; Pengfei Lin; Dong Zhang; Shuangwu Liu (Brain Imaging and Behavior, 2024)

Enhanced catalytic performance and N2 yield of Ag/CeO2 catalyst by Cu modification for NVOCs removal - Xiaohan Guo; Fanshun Lin; Meixingzi Gao; Qiguang Dai; Wangcheng Zhan; Li Wang; Yun Guo; Aiyong Wang; Yanglong Guo (Chemical Engineering Journal, 2024)

Roles and sources of B vitamins in the marine ecosystem - Lin Wang; Hancheng Zhao; Ran Bi; Xiaohan Chen; Zhendong Lyu; Wenhua Liu (Reviews in Fish Biology and Fisheries, 2024)

Performance and mechanism of sequential UV-NaClO disinfection: Inactivation and reactivation of antibiotic-resistant bacteria, disinfection byproduct formation and microbial community variation - Lihua Cheng; Xiaohan Wei; Aili Gao; Lin Zhou; Xueqing Shi; Xiaolin Zhou; Xuejun Bi; Tang Yang; Shujuan Huang (Journal of Water Process Engineering, 2024)

Evaluating city road dust emission characteristics with a dynamic method: A case study in Luoyang, China - Jiawei Chen; Hanyang Man; Wenying Cai; Laichang Lin; Xiaoduo Chen; Xiaohan Shao; Yumeng Bao; Bo Zhu; Lizhong Xu (Science of The Total Environment, 2023)

Bioconcentration of polycyclic aromatic hydrocarbons in different tissues of zebrafish (Danio rerio) investigated with PBTK model - Yawei Zhai; Haotian Wang; Xiaohan Lin; Xinghui Xia (Environmental Science and Pollution Research, 2023)

Remediation of arsenic contaminated water and soil using mechanically (ball milling) activated and pyrite-amended electrolytic manganese slag - Zhihao Ha; Mengyu Ma; Xiaohan Tan; Yanxin Lan; Yanmin Lin; Tian C. Zhang; Dongyun Du (Environmental Research, 2023)

Efficient detection of nitrite in water based on an Au/NiO/Rh trimetallic composite modified laser-induced graphene electrode prepared by one-step electrodeposition - Zeyu Liu; Xiaohan Shan; Qiang Xue; Yao Liu; Lin He; Haijiao Xie (Chemical Engineering Journal, 2023)

Bioavailability of micro/nanoplastics and their associated polycyclic aromatic hydrocarbons to Daphnia Magna: Role of ingestion and egestion of plastics - Yao Li; Xinghui Xia; Jie Zhang; Xiaohan Lin; Yidi Zhang; Haotian Wang; Yang Li; Qing Zhang; Shangwei Zhang (Science of The Total Environment, 2023)

Asymmetric impacts of El Niño–Southern Oscillation on the winter precipitation over South China: the role of the India–Burma Trough - Xiaohan Lin; Bo Lu; Gen Li; Chujie Gao; Lin Chen (Climate Dynamics, 2023)

B vitamins supplementation induced shifts in phytoplankton dynamics and copepod populations in a subtropical coastal area - Lin Wang; Hancheng Zhao; Edmond Sanganyado; Bo Liang; Xiaohan Chen; Qun Ma; Jianqing Lin; Wenhua Liu (Frontiers in Marine Science, 2023)
Introduction B vitamins play a crucial role in shaping phytoplankton and zooplankton communities in marine ecosystems, yet their impact on community dynamics remains poorly understood. Methods We carried out in situ incubation experiments of B vitamins supplementation to explore the response pattern of phytoplankton and zooplankton community compositions. Results The results showed that vitamins B 1 , B 2 , B 6 and B 12 promoted the growth of phytoplankton, and the total Chl α in 87.5% of the supplemented B vitamin treatments showed a significant positive response (p < 0.05). Supplementation with these B vitamins significantly altered the community composition of phytoplankton, and 75% of the B vitamin-supplemented treatments showed an increase in the relative abundance of Minutocellus , Thalassiosirales, Odontella , Prymnesiales and Ditylum , considered mainly to be the result of B vitamin auxotrophy. In contrast, a significant decrease in Copepoda, including Calanoida and Cyclopoida, was observed in 87.5% of treatments. The observed shifts in community composition were attributed to the auxotrophy of certain diatoms and Prymnesiales for B vitamins. These shifts subsequently led to negative correlations (Spearman Rho < -0.8) between the abundance of these phytoplankton species and Copepoda populations. Discussion These findings advance our understanding of the complex interactions between micronutrient availability and plankton community dynamics.

The characteristics and origin of chlorite coats in the Oligocene gas sandstone reservoirs of the Upper Huagang Formation, Xihu Depression, East China Sea Shelf Basin - Jianli Lin; Chengyan Lin; Pengjie Ma; Chunmei Dong; Binbin Liu; Xin Huang; Xianguo Zhang; Xiaohan Zhao (Sedimentary Geology, 2023)

Impact of Revised Trigger and Closure of the Double-Plume Convective Parameterization on Precipitation Simulations over East Asia - Xiaohan Li; Yi Zhang; Yanluan Lin; Xindong Peng; Baiquan Zhou; Panmao Zhai; Jian Li (Advances in Atmospheric Sciences, 2023)

Quantifying tree canopy coverage threshold of typical residential quarters considering human thermal comfort and heat dynamics under extreme heat - Yingnan Li; Dongli Lin; Yuhan Zhang; Zipeng Song; Xiaohan Sha; Siqi Zhou; Cen Chen; Zhaowu Yu (Building and Environment, 2023)

Accelerated removal of five pesticide residues in three vegetables with ozone microbubbles - Xiaohan Li; Chengcheng Liu; Fengmao Liu; Xianzhao Zhang; Qingrong Peng; Ge Wu; Jin Lin; Zhanping Zhao (Food Chemistry, 2023)

A critical thermal transition driving spring phenology of Northern Hemisphere conifers - Jian‐Guo Huang; Yaling Zhang; Minhuang Wang; Xiaohan Yu; Annie Deslauriers; Patrick Fonti; Eryuan Liang; Harri Mäkinen; Walter Oberhuber; Cyrille B. K. Rathgeber; Roberto Tognetti; Václav Treml; et al. (Global Change Biology, 2023)
Despite growing interest in predicting plant phenological shifts, advanced spring phenology by global climate change remains debated. Evidence documenting either small or large advancement of spring phenology to rising temperature over the spatio‐temporal scales implies a potential existence of a thermal threshold in the responses of forests to global warming. We collected a unique data set of xylem cell‐wall‐thickening onset dates in 20 coniferous species covering a broad mean annual temperature (MAT) gradient (−3.05 to 22.9°C) across the Northern Hemisphere (latitudes 23°–66° N). Along the MAT gradient, we identified a threshold temperature (using segmented regression) of 4.9 ± 1.1°C, above which the response of xylem phenology to rising temperatures significantly decline. This threshold separates the Northern Hemisphere conifers into cold and warm thermal niches, with MAT and spring forcing being the primary drivers for the onset dates (estimated by linear and Bayesian mixed‐effect models), respectively. The identified thermal threshold should be integrated into the Earth‐System‐Models for a better understanding of spring phenology in response to global warming and an improved prediction of global climate‐carbon feedbacks.

PM2.5 induces the abnormal lipid metabolism and leads to atherosclerosis via Notch signaling pathway in rats - Tianyang Zhao; Xu Li; Honghao Qian; Xiaohan Miao; Ying Zhu; Jia Wang; Ju Hui; Liting Zhou; Lin Ye (Toxicology, 2023)

Dermal Uptake is an Important Pathway for the Bioconcentration of Hydrophobic Organic Compounds by Zebrafish (Danio rerio) - Yilin Xiao; Xiaohan Lin; Haotian Wang; Xinghui Xia (Bulletin of Environmental Contamination and Toxicology, 2023)

Oral Magnesium Supplementation for the Prevention of Preeclampsia: a Meta-analysis or Randomized Controlled Trials - Jing Yuan; Ying Yu; Tongyu Zhu; Xiaohan Lin; Xincheng Jing; Juan Zhang (Biological Trace Element Research, 2022)

A review on the removal of phthalate acid esters in wastewater treatment plants: from the conventional wastewater treatment to combined processes - Lin Bai; Xiaowan Dong; Fangshu Wang; Xiaohan Ding; Zhikai Diao; Dong Chen (Environmental Science and Pollution Research, 2022)

Chemical constituents from the fruits of Piper longum L. and their vascular relaxation effect on rat mesenteric arteries - Dan Li; Rui Wang; Xiaohan Cheng; Jianfeng Yang; Yihui Yang; Huichong Qu; Sen Li; Shan Lin; Donghua Wei; Yuhua Bai; Xiaodong Zheng (Natural Product Research, 2022)

Experimental and Numerical Investigations on the Macro-Meso Shear Mechanical Behaviors of Artificial Rock Discontinuities with Multiscale Asperities - Xinrong Liu; Bin Xu; Guangyi Lin; Junhui Huang; Xiaohan Zhou; Yingkun Xie; Jiwen Wang; Fei Xiong (Rock Mechanics and Rock Engineering, 2021)

Effects of mutual grafting Solanum photeinocarpum from two ecosystems on physiology and selenium absorption of their offspring under selenium stress - Kewen Huang; Yan Wang; Xiaohan Wei; Yuhui Bie; Huixuan Zhou; Lili Deng; Lijin Lin; Ming’an Liao (Acta Physiologiae Plantarum, 2021)

Construction of an infectious full-length cDNA clone of potato aucuba mosaic virus - Buyang Chen; Qi Lin; Yueyan Yin; Liangliang Jiang; Fang Wang; Shuzhen Hu; Xinyang Wu; Fei Xu; Jiejun Peng; Hongying Zheng; Chengqi Yan; Xiaohan Mo; et al. (Archives of Virology, 2021)

Population-based meta-analysis of chloroquine: informing chloroquine pharmacokinetics in COVID-19 patients - Xueting Yao; Xiaoyu Yan; Xiaohan Wang; Ting Cai; Shun Zhang; Cheng Cui; Xiaoxu Wang; Zhe Hou; Qi Liu; Haiyan Li; Jing Lin; Zi Xiong; et al. (European Journal of Clinical Pharmacology, 2021)
Aims Chloroquine (CQ) has been repurposed to treat coronavirus disease 2019 (COVID-19). Understanding the pharmacokinetics (PK) in COVID-19 patients is essential to study its exposure–efficacy/safety relationship and provide a basis for a possible dosing regimen optimization. Subject and methods In this study, we used a population-based meta-analysis approach to develop a population PK model to characterize the CQ PK in COVID-19 patients. An open-label, single-center study (ethical review approval number: PJ-NBEY-KY-2020-063-01) was conducted to assess the safety, efficacy, and pharmacokinetics of CQ in patients with COVID-19. The sparse PK data from 50 COVID-19 patients, receiving 500 mg CQ phosphate twice daily for 7 days, were combined with additional CQ PK data from 18 publications. Results A two-compartment model with first-order oral absorption and first-order elimination and an absorption lag best described the data. Absorption rate (ka) was estimated to be 0.559 h −1 , and a lag time of absorption (ALAG) was estimated to be 0.149 h. Apparent clearance (CL/F) and apparent central volume of distribution (V2/F) was 33.3 l/h and 3630 l. Apparent distribution clearance (Q/F) and volume of distribution of peripheral compartment (Q3/F) were 58.7 l/h and 5120 l. The simulated CQ concentration under five dosing regimens of CQ phosphate were within the safety margin (400 ng/ml). Conclusion Model-based simulation using PK parameters from the COVID-19 patients shows that the concentrations under the currently recommended dosing regimen are below the safety margin for side-effects, which suggests that these dosing regimens are generally safe. The derived population PK model should allow for the assessment of pharmacokinetics–pharmacodynamics (PK-PD) relationships for CQ when given alone or in combination with other agents to treat COVID-19.

Ultraviolet photolysis of metformin: mechanisms of environmental factors, identification of intermediates, and density functional theory calculations - Wenting Lin; Xiaohan Zhang; Ping Li; Yongzhen Tan; Yuan Ren (Environmental Science and Pollution Research, 2020)

A20 reduces lipid storage and inflammation in hypertrophic adipocytes via p38 and Akt signaling - Luoyan Ai; Xiaohan Wang; Zhiwei Chen; Qing Lin; Dazhi Su; Qingqing Xu; Changwei Wu; Xiaoke Jiang; Antao Xu; Zhuping Fan (Molecular and Cellular Biochemistry, 2016)

Exact timing of granulite metamorphism in the Namche-Barwa, eastern Himalayan syntaxis: new constrains from SIMS U–Pb zircon age - Wen Su; Ming Zhang; Xiaohan Liu; Jinfu Lin; Kai Ye; Xin Liu (International Journal of Earth Sciences, 2012)

The Endo-β-Mannanase gene families in Arabidopsis, rice, and poplar - Joshua S. Yuan; Xiaohan Yang; Jingru Lai; Hong Lin; Zong-Ming Cheng; Hiroyuki Nonogaki; Feng Chen (Functional & Integrative Genomics, 2006)